Enhancing CO2 absorption for post-combustion carbon capture via zinc-based biomimetic catalysts in industrially relevant amine solutions. (June 2019) - Widger, Leland R.; Sarma, Moushumi; Kelsey, Rachael A.; Risko, Chad; Lippert, Cameron A.; Parkin, Sean R.; Liu, Kunlei
Highlights: A series of Carbonic Anhydrase mimics were synthesized as CO2 hydration catalysts for enhancing CO2 absorption into carbon capture solvents. Ancillary chloride ligands and a hydrophobic binding pocket are shown to be key features for activity of the catalysts. DFT simulations suggest that [ZnII(PSAAMP)Cl2] and [ZnII(PSAMEA)Cl2] are catalyzing the CO2 hydration analogous to CA enzyme. [ZnII(PSAAMP)Cl2] and [ZnII(PSAMEA)Cl2] are stable in harsh thermal and oxidative conditions with projected lifetimes >1500 h. [ZnII(PSAAMP)Cl2] and [ZnII(PSAMEA)Cl2] exhibit 2–5 times greater enhancement in mass transfer than previous catalysts. Abstract: Anthropogenic greenhouse gas emissions, such as CO2 from fossil fuel combustion, are a global environmental, health, and economic concern. Aqueous amine-based CO2 capture processes offer a technologically mature and relevant approach to CO2 sequestration, although cost reduction strategies are still necessary for widespread deployment. Inspired by the metalloenzyme carbonic anhydrase (CA), we report the design, synthesis, and activity testing of zinc(II) complexes [Zn II (PSA AMP )Cl2 ] (1 ) and [Zn II (PSA MEA )Cl2 ] (2 ) as CO2 hydration catalysts in aqueous amine solutions. The novel multifunctional ligand environment includes features in the primary and secondary coordination spheres that result in enhanced CO2 mass transfer in industrially relevant carbon capture solvents and stability towards harsh industrial process conditions. Complexes that lack these key features do not show enhanced CO2 absorption. Density functional theory (DFT) calculations that assess the catalytic pathway demonstrate how1 and2 catalyze CO2 hydration analogous to CA. These catalysts increase mass transfer by 20–55% in lab scale experiments, offering the potential to reduce the cost of amine-based CO2 capture processes without significantly altering industrial-scale system design, making rapid deployment of this critical bridge technology a viable strategy to reduce global greenhouse gas emissions.